Síndrome de burnout entre internos de medicina da universidade federal de Sergipe e a contribuição do grupo balint para sua prevenção - Calcides, Dâmaris Alejandra Paula (2019)
BACKGROUND: We intend to estimate the Burnout Syndrome (BS) prevalence and associated factors among medical internship students at a public university in northeastern Brazil, besides to investigate the Balint Group (BG) contribution in its prevention. METHODS: It was conducted a cross-sectional study in February/2018 with Medical Internship Students at the University researched. It was applied a structured questionnaire developed by the authors about socio-demographic data, educational process with BG participation and current psycho-emotional experiences besides the Maslach Burnout Inventory – Student Survey (MBI-SS), for BS screening. It was performed descriptive data analysis, logistic regression and cluster analysis. RESULTS: It was participated 184 students (98%), with a mean age of 25.9±3.9 years, of which 54.9% were men. The prevalence of BS was 10.3% by the three-dimensional criterion and 35.9% by the two-dimensional criterion (Exhaustion and Cynicism), being higher in those who thought to drop-out of the undergraduate (OR=2.14), were dissatisfied with the teaching strategies (OR=2.67) and its performance (OR=2.64) and made use of licit drugs (OR=2.37). The variables associated to BS allowed the individuals to be discriminated, classifying them into three subgroups. BS prevalence decreased, and vulnerability factors were attenuated when there was a higher frequency of students participating in BG. CONCLUSIONS: The prevalence of two-dimensional BS was high with factors associated with the educational process. Participation in BG was associated with a reduction in BS prevalence. Longitudinal studies should be conducted